Pengaruh Profitability, Capital Intensity, Inventory Intensity Terhadap Tax Avoidance Dengan Dewan Komisaris Sebagai Variabel Moderasi (Studi Kasus Pada Perusahaan Manufaktur Di BEI 2021-2023) - Eva Cahyaningrum; Kiryanto (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the effect of profitability, capital intensity and inventory intensity on tax avoidance with the board of commissioners as a moderating variable. This study uses a quantitative approach with secondary data research through annual reports. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2021 to 2023. The sampling technique used was purposive sampling. Based on the results of this technique, data was obtained for 213 companies. The data analysis technique in this study used multiple linear regression analysis which was processed using the SPSS version 26 software application. The results of this study indicate that Profitability has a positive and significant effect on tax avoidance. Capital intensity has a negative and significant effect on tax avoidance. Inventory intensity has a negative and significant effect on tax avoidance. The board of commissioners weakens and significantly affects the relationship between Profitability and tax avoidance. The board of commissioners strengthens and significantly affects the relationship between capital intensity and tax avoidance. The board of commissioners strengthens and significantly affects the relationship between Inventory integrity and tax avoidance.